A DESCRIPTIVE STUDY OF THE SHIFT OF ROLES BETWEEN A TEACHER AND STUDENTS IN ENGLISH CLASSROOM DISCOURSE - Suwandi, Doni Ramdhani (2015)
Abstract: This study was aimed to figure out the exchange patterns during classroom interaction and its relation to the shift of roles of serving primary knower between a teacher and students. Thirty nine students of twelfth grade and an English teacher in a public senior high school in Bandung were involved as the participants. This study employed a descriptive-qualitative method, and the main data were classroom observation transcript and teacher's interview transcript. The data analysis was done by applying classroom discourse analysis through coding and categorizing utterances of teacher and students into exchange categories proposed by Suherdi (2009). The findings reveal that both Non-Anomalous (Knowledge-Oriented and Action-Oriented) and Anomalous Exchanges (Elliptical, Defective, and Broken) were found in the interaction between the teacher and the students, therefore the exchange categories affect the shift of roles of serving primary knower between teacher and students. With regard to the findings, two exchanges were likely to be dominant among other exchanges throughout four meetings of the lesson; those are DK1-initiated exchanges (30.19%) and A1-initiated exchanges (34.57%). Keywords: Classroom discourse analysis, Classroom Interaction, Shift of Roles Abstrak: Penelitian ini bertujuan untuk mengetahui pola baku tutur di dalam interaksi kelas, dan hubungannya dengan pergantian peran antara guru dan siswa dalam hal sumber utama pengetahuan. Tiga puluh sembilan siswa kelas 12 dan seorang guru Bahasa Inggris di sebuah sekolah menengah atas negeri di Bandung terlibat sebagai partisipan. Penelitian ini menggunakan metode deskriptif-kualitatif, dan data utama yang digunakan adalah transkrip observasi kelas dan transkrip wawancara guru. Analisis data dilakukan dengan menggunakan analisis wacana kelas dengan memberi kode dan mengkategorikan ujaran guru dan siswa ke dalam kategori baku tutur yang dikembangkan oleh Suherdi (2009). Temuan menunjukan bahwa baku tutur non-anomalous (knowledge-oriented and action-oriented) dan baku tutur anomalous (elliptical, defective, and broken) ditemukan di dalam interaksi guru dan siswa. Selain itu, oleh karena itu kategori baku tutur mempengaruhi pergantian peran antara guru dan siswa dalam hal sumber utama pengetahuan. Berdasarkan temuan, dua baku tutur cenderung dominan di antara baku tutur yang lain di seluruh empat pertemuan pelajaran, yaitu baku tutur DK1-initiated (30.19%) and baku tutur A1-initiated (34.57%). Kata kunci: analisis wacana kelas, interaksi kelas, pergantian peran antara guru dan siswa